KINERJA SATUAN POLISI PAMONG PRAJA DALAM KEBIJAKAN PEMBINAAN DAN PENERTIBAN PEDAGANG KAKI LIMA DI TAMAN PANCASILA KABUPATEN KARANGANYAR - Joko Pramono & Aris Tri Haryanto, Huri Kusmini (Transformasi, 2014)
This study aims to analyze the performance of Civil Service Police Unit in the development of policy and enforcement on Street Vendor in Pancasila Park Karanganyar and the barriers experienced by municipal police in policy development and enforcement on Street Vendor in Pancasila Park Karanganyar The presence of street vendors is one of the factors causa problem in both the problem of hygiene in each region as well as in Karanganyar. Various problem associated with street vendors are emerging that turned out to harm the public and local governments also own such discomfort because the existence of street vendors is not in right place (using public space to sell) that interfere with the daily activities of the community. Keywords : performance, policies, vendors.